Prostate vascular flow: The effect of the ejaculation on the power doppler ultrasonographic examination. (11th September 2017) - Alonge, S; Melandri, M; Fanciullo, L; Lacalandra, GM; Aiudi, G
Contents: Power Doppler sonography (PD) can accurately depict tissue perfusion, recognize slow flows, and is relatively angle independent. The monitoring of local blood flow by Doppler ultrasonography is helpful in differentiating prostatic physio‐pathological conditions, but the recognizing of physiological variables that could affect it is crucial to apply this technique in clinical practice. This study aimed to evaluate if ejaculation affects blood flow to the prostate and to state how long this effect lasts. Serial PD examinations of prostate were performed in 18 dogs (1–5 years, 6–40 kg) immediately before (T0) and after (T1) the ejaculation, and repeated 6 (T2), 18 (T3) and 24 (T4) hours later. For each examination, two representative PD images were chosen and ranked by two independent observers according to the following scoring system: 0 = mild subcapsular (S) vascularization without clear evidence of parenchymal (P) vascularization; 1 = moderate P and S vascularization; 2 = severe S and moderate P vascularization; 3 = severe P and moderate S vascularization; 4 = severe P and S vascularization. Interobserver agreement was assessed using Kappa of Cohen. Ranked data, grouped according to time, were compared by ANOVA and Tukey HSD test ( p < .05). Variations in the vascular flow pattern at different times were observed for all dogs. The statistical analysis evidenced a significant difference for T0 vs T1 and vs T2 and vs T3 ( p < .01), with no significant difference for T0 vs T4 ( p > .05). Interobserver agreement was very good (Kappa of Cohen = 0.86). This study demonstrated a definite increase in vascular flow to the prostate after ejaculation. The present results suggest a minimum of 24 hr sexual rest before the PD examination of the gland. This result should be taken into account whenever Doppler sonography is used to evaluate potential hyperaemia in dogs suspected of having prostate abnormalities.